Social marketing through communication campaigns: the APAV case - Machado, Ana Teresa (2015)
Social responsability is gaining its momentum in the formulation of the strategy of the organizations, at the organizational, behavioral and communicational level, and for many organizations it is even considered a key differentiator and a proximity element to customers, whom are increasingly sensitive to individual and collective well-being (Carrol & Shabanna, 2010). Yet, welfare is not the prerogative only of companies, but also of non-profit organizations, which include it on their activity as a goal in itself. And for many of these, social causes are the main reason for their existence. This research focuses on one of these non-profit organizations - APAV - whose mission is the prevention, the combat and the protection of victims of domestic violence. Our object of study is one its recent mass media campaigns, that aim to alert and modify the behavior of the various actors involved in the process (victims, witnesses, society in general). A quantitative research has been conducted, operated by the application of questionnaire surveys to a sample of 134 subjects that seeks to assess to extent to which the emotions elicited by watching an APAV campaign influence behavior towards domestic violence, considering the mediating role of attitudes and subjective norms. The results measured by means of Structural Equation Modeling (SEM), show the validation of only two working hypotheses under study, indicating that the attitude towards advertising has a positive effect on attitudes towards domestic violence influencing in turn, behavioral intention of subjects. The main social and academic contributions of this research are discussed.